-6=-6w+4(w+3)

Simple and best practice solution for -6=-6w+4(w+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=-6w+4(w+3) equation:


Simplifying
-6 = -6w + 4(w + 3)

Reorder the terms:
-6 = -6w + 4(3 + w)
-6 = -6w + (3 * 4 + w * 4)
-6 = -6w + (12 + 4w)

Reorder the terms:
-6 = 12 + -6w + 4w

Combine like terms: -6w + 4w = -2w
-6 = 12 + -2w

Solving
-6 = 12 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
-6 + 2w = 12 + -2w + 2w

Combine like terms: -2w + 2w = 0
-6 + 2w = 12 + 0
-6 + 2w = 12

Add '6' to each side of the equation.
-6 + 6 + 2w = 12 + 6

Combine like terms: -6 + 6 = 0
0 + 2w = 12 + 6
2w = 12 + 6

Combine like terms: 12 + 6 = 18
2w = 18

Divide each side by '2'.
w = 9

Simplifying
w = 9

See similar equations:

| 4b^2-169y^2= | | 9x+3x=10101010101001101 | | c+bc-11c-4=13c+4-2 | | 2k+10=k+15 | | (8/t-7)-3/t | | 15=2a-2 | | 18+6x+x^2=0 | | 5x-5y=10z | | -4/35/8/7 | | 2(4x+8)=x+7x-2 | | -7=-7x+3(x+5) | | -a+2a=4a+6-2 | | -3y=6/5 | | -4x/7=-12 | | 6x=-6x+144 | | 6x-15=5x-9 | | 5/-5 | | x-3/x= | | 6x/39 | | -5/9w=35 | | 44.95(t-25)=2511.6 | | (a+3b)+(3a-b)i=6+6i | | x×x-3/x= | | x×x-3/x=18 | | 4x^2=57 | | 10v-3=8v+9 | | 3y-3(-33)=2y+2(-33) | | 4b+4b+4b= | | 2=9z-3z+2-6z+4+z | | 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= |

Equations solver categories